Intolerance in Islamic textbooks: The quest for an Islamic teaching model for Indonesian schools - Ikhrom Ikhrom; Irwan Abdullah; Reza Kafipour; Zulfi Mubaraq; Agus Sutiyono (Cogent Education, 2023)
AbstractThe study highlights the presence of intolerance within the textbooks used for Islamic education, which has negative implications for peace and harmony. However, the understanding of this intolerance construction in the textbooks is currently limited. Therefore, this research aims to identify and analyze the intolerant values embedded within these textbooks’ language, content, and scenarios. The ultimate goal is to develop an action plan to prevent the dissemination of intolerance through the education system. To achieve this objective, qualitative methods such as content analysis, interviews, and focus group discussions were employed to collect and analyze data. The study’s findings indicate the following: a) The textbooks used for Islamic education can foster and promote intolerant beliefs, attitudes, and behaviors among students, who may mistakenly associate these with the teachings of Islam. b) The narratives promoting intolerance found within the textbooks result from negligence during the writing, reviewing, and editing processes. C) The development of new textbooks is necessary, and it should be a collaborative effort involving intellectuals, religious and cultural leaders, with a focus on promoting values of peace and social harmony. In conclusion, the study recommends a comprehensive mapping of the textbooks used in Islamic education at different education levels to identify and address any potential threats to peace. If strategically approached, Islamic education can serve as a platform for nurturing students’ moral foundations and fostering peaceful coexistence within society.